Pengembangan Pendidikan Islam di Perguruan Tinggi Berbasis Pesantren di Sekolah Tinggi Agama Islam Bustanululum Krai Kecamatan Yosowilangun Lumajang - Syaichol Imam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the development of Islamic education in pesantren-based higher education at Sekolah Tinggi Agama Islam Bustanul Ulum Krai, Yosowilangun District, Lumajang. Using a qualitative approach, this research explores the education development process and its impact on the community. The findings indicate that this institution plays a crucial role in improving human resource quality through formal and non-formal education while contributing to community development. In addition to its benefits, this study also highlights the challenges faced, particularly in adapting to technological advancements and social changes in the modern era. Pesantren are expected to balance traditional values with educational innovation to remain relevant and competitive. These findings provide insights for policymakers and education practitioners in designing strategies for developing Islamic education in pesantren-based institutions amidst evolving societal dynamics.